PENGEMBANGAN POTENSI WISATA TREKKING KAWAH RATU, DESA WISATA GUNUNGSARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT: wisata petualangan, trekking, desa wisata, potensi wisata, pengembangan wisata - Aisyianita, Revi Agustin; Nisya Nisrina (Family Welfare Education, 2025)
Gunungsari Tourism Village holds significant potential for tourism development, particularly in the adventure-based tourism sector. Kawah Ratu, located within Gunungsari Tourism Village, presents opportunities to be developed as a destination for adventure trekking. Its natural beauty, biodiversity, and challenging trekking routes make it an attractive destination for nature and adventure enthusiasts. This study aims to identify and analyze the potential and opportunities for developing adventure trekking activities at Kawah Ratu. The research employs a descriptive qualitative approach through field observations, interviews, and literature review related to adventure tourism development. The findings indicate that Kawah Ratu possesses great potential as an adventure tourism destination due to its rich natural environment, unique trekking paths, and embedded local legends. However, challenges such as limited accessibility, lack of supporting facilities, and insufficient local human resource capacity in tourism management still exist. Nevertheless, there are vast opportunities for development through stakeholder collaboration, human resource training, and digital-based promotion. This study is expected to serve as a reference for designing sustainable adventure tourism development strategies in Kawah Ratu.